Intensitas Penggunaan Gadget dan Kualitas Tidur Mahasiswa Keperawatan - Suryani; Hasna'Sabila Fasya; Zubaida Rohmawati (Jurnal Riset Keperawatan dan Kesehatan, 2026)
Background: Poor sleep quality is a common health problem among university students, particularly Gen Z nursing students who experience high academic demands and intensive gadget use. Excessive gadget use, especially before bedtime, can disrupt circadian rhythms and reduce sleep quality, leading to negative impacts on physical and mental health as well as academic performance. Objective: This study aimed to analyze the relationship between gadget use intensity and sleep quality among Gen Z nursing students at Universitas ‘Aisyiyah Yogyakarta. Methods: This study employed a quantitative design with a cross-sectional approach. The sample consisted of 135 third-semester nursing students selected using a cluster random sampling technique. Gadget use intensity was measured using the Smartphone Addiction Scale–Short Version (SAS-SV), while sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using univariate and bivariate analyses with the Chi-Square test. Results: The results showed that most respondents had a high level of gadget use intensity (48.1%) and poor sleep quality (86.7%). The Chi-Square test indicated a p-value of 0.000 (p < 0.05), demonstrating a significant relationship between gadget use intensity and sleep quality. Conclusion: There is a significant relationship between gadget use intensity and sleep quality among Gen Z nursing students at Universitas ‘Aisyiyah Yogyakarta. Higher gadget use intensity is associated with poorer sleep quality.